Electrode adhesive as well as preparation method and application thereof

By using the electrode adhesive prepared by combining water-soluble polymers and amino-containing polymers, the existing electrode adhesives have been solved, but the problems of high adhesion but insufficient flexibility, poor electrolyte swelling resistance and insufficient temperature stability in lithium-ion batteries, and the effects of high adhesion performance, good flexibility and electrolyte swelling resistance are achieved.

CN119614104APending Publication Date: 2025-03-14ANHUI HAOFEI NEW MATERIAL CO LTD +2

Patent Information

Application Number
CN202411936869.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing electrode adhesives have problems in lithium-ion batteries, such as high adhesion but insufficient flexibility, poor electrolyte swelling resistance and insufficient temperature stability.

Method used

Electrode binder prepared by a water-soluble polymer obtained by polymerization and alcoholylation reaction of monomers and amino-containing polymers were used. The polymer side chain is rich in hydroxy, carboxyl and cyano groups, which can form a crosslinking network, improve cohesion and bonding properties, and improve carrier migration.

Benefits of technology

It achieves high bonding performance, good flexibility, resistance to electrolyte swelling and high temperature stability, and is suitable for electrode materials for lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211711200000141
    Figure BDA0005211711200000141
  • Figure BDA0005211711200000151
    Figure BDA0005211711200000151
  • Figure BDA0005211711200000171
    Figure BDA0005211711200000171
Patent Text Reader

Abstract

The invention relates to an electrode adhesive as well as a preparation method and application thereof. The electrode adhesive comprises a water-soluble high-molecular polymer and an amino-containing polymer, the water-soluble high-molecular polymer is obtained by sequentially carrying out polymerization reaction and alcoholysis reaction on monomers; the monomers comprise a type I monomer, a type II monomer and a type III monomer; the monomer I comprises vinyl acetate and / or vinyl propionate; the monomer II comprises methacrylate containing short-chain alkane and / or acrylate containing short-chain alkane; and the III type monomer contains cyano groups. The electrode adhesive provided by the invention has good adhesive property, flexibility and temperature stability, is resistant to electrolyte swelling, and is suitable for an electrode material of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to an electrode adhesive and a preparation method and application thereof. Background Art

[0002] In recent years, the rapid development of new energy vehicles has greatly promoted the development of the lithium-ion battery industry. As an essential additive in lithium-ion batteries, binders play two main roles in batteries. On the one hand, they bond scattered active materials into a regular whole, giving electrode materials good mechanical properties, which is helpful for subsequent processing and production; on the other hand, they bond active materials to current collectors to prevent short circuits caused by the shedding of active materials, thereby ensuring the normal operation of the battery. It can be seen that the choice of binders has an important impact on lithium-ion batteries.

[0003] As an additive, the binder generally accounts for only about 1% of the entire electrode material. At such a low addition amount, in order to ensure adequate performance, extremely high requirements are placed on the quality of the binder itself. First, it is required to have excellent bonding properties; second, since the binder will be in contact with the electrolyte for a long time during the operation of the battery, it is required to be able to resist the dissolution and swelling of the electrolyte to avoid performance degradation; finally, considering that the battery will be affected by environmental changes and heat generated by internal resistance during use, the binder is required to have excellent temperature stability.

[0004] At present, the negative electrode binders mainly used in the market include two categories: one is a flexible system of styrene-butadiene emulsion (SBR) and sodium carboxymethyl cellulose (CMC). This system has the advantages of high bonding strength and good flexibility, but it also has limitations such as large electrode rebound and high electrolyte swelling rate; the other is polyacrylic acid (PAA), polyacrylate and its derivative system. This system has the advantages of high cohesion, low electrolyte swelling rate and high thermal stability, but it also has problems such as insufficient flexibility and difficulty in processing.

[0005] Therefore, providing an adhesive with high adhesion, good flexibility, resistance to electrolyte swelling and high temperature stability is a technical problem that needs to be solved in the current field. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide an electrode adhesive and a preparation method and application thereof. Compared with the prior art, the electrode adhesive provided by the present invention has good bonding properties, flexibility and temperature stability, and is resistant to electrolyte swelling, and is suitable for electrode materials of lithium-ion batteries.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an electrode binder, the electrode binder comprising a water-soluble high molecular polymer and an amino-containing polymer;

[0009] The water-soluble high molecular polymer is obtained by sequentially performing polymerization reaction and alcoholysis reaction on monomers;

[0010] The monomers include Class I monomers, Class II monomers and Class III monomers;

[0011] The Class I monomers include vinyl acetate and / or vinyl propionate;

[0012] The class II monomers include methacrylates containing short-chain alkanes and / or acrylates containing short-chain alkanes;

[0013] The class III monomers contain a cyano group.

[0014] The water-soluble high molecular polymer used in the electrode adhesive provided by the present invention is obtained by sequentially performing polymerization reaction and alcoholysis reaction of monomers, wherein the monomers undergo free radical polymerization reaction to obtain millimeter-sized solid polymer particles, and then the solid polymer particles undergo alcoholysis reaction in a strong alkaline alcohol solution, the ester group in the alkyl ester or carboxylate of the polymer side chain is decomposed, and the hydroxyl and carboxylate groups are left on the side chain of the polymer, and the linear polymer chain is converted from lipophilic to hydrophilic, and the small molecules are removed by filtration. Therefore, the water-soluble high molecular polymer provided by the present invention can form hydrogen bonds with the hydroxyl groups on the surface of the electrode negative electrode material through the hydroxyl groups on the side chain, thereby forming a cross-linked network in the electrode active material, further improving the cohesive force; on the other hand, the side chain of the water-soluble high molecular polymer provided by the present invention contains cyano groups, which can effectively improve carrier migration and contribute to the improvement of battery performance. On this basis, the adhesive provided by the present invention is compounded by using a water-soluble high molecular polymer and an amino-containing polymer. The addition of the amino polymer can provide more abundant cross-linking sites for the linear water-soluble high molecular polymer, form a more solid network structure, and effectively disperse the internal stress of the polymer itself, thereby improving the flexibility and processing performance of the electrode plate.

[0015] Preferably, the amino-containing polymer includes any one of polyethyleneimine, polymelamine or polymelamine formal, or a combination of at least two thereof.

[0016] Preferably, the short-chain alkane in the Class II monomer includes an alkane with a carbon number of ≤4, and the carbon number may be, for example, 1, 2, 3 or 4, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the type II monomer includes any one of methyl acrylate, methyl methacrylate, butyl acrylate or ethyl acrylate, or a combination of at least two thereof.

[0018] Preferably, the Class III monomers include acrylonitrile and / or methacrylonitrile.

[0019] Preferably, the raw materials for the polymerization reaction further include water, protective colloid, electrolyte and initiator.

[0020] Preferably, the protective colloid comprises polyvinyl alcohol and / or polyvinyl pyrrolidone.

[0021] Preferably, the electrolyte comprises sodium bicarbonate and / or sodium sulfate.

[0022] Preferably, the initiator comprises an azo compound and / or a peroxide.

[0023] Preferably, the azo compound includes azobisisoheptanitrile and / or azobisisobutyronitrile.

[0024] Preferably, the peroxide comprises diisopropyl peroxydicarbonate and / or lauroyl peroxide.

[0025] Preferably, the raw materials for the polymerization reaction include, by weight, 20-70 parts of Class I monomers, for example, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts or 70 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; 10-40 parts of Class II monomers, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; 1-20 parts of Class III monomers, for example, 1 part, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts or 20 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; 0.1-0.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable; 1-5 parts of protective glue, for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable; 0.1-0.5 parts of electrolyte, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable; 150-300 parts of water, for example, 150 parts, 160 parts, 180 parts, 200 parts, 220 parts, 240 parts, 260 parts, 280 parts or 300 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable.

[0026] Preferably, the mass ratio of the Class I monomer, Class II monomer and Class III monomer is (40-60):(15-25):(5-15), for example, it can be 40:15:5, 45:17:7, 50:18:9, 55:20:11 or 60:25:15, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In the present invention, by preferably controlling the mass ratio of the type I monomer, the type II monomer and the type III monomer, the ratio of the hydroxyl group, the carboxyl group and the cyano group in the adhesive molecule can be effectively controlled, thereby providing compatibility.

[0028] Preferably, the weight average molecular weight of the water-soluble high molecular weight polymer is 500-1000 kDa, for example, it can be 500 kDa, 550 kDa, 600 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 950 kDa or 1000 kDa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the raw materials for the alcoholysis reaction include a polymer, an alcohol solvent, a strong base and water.

[0030] Preferably, the alcohol solvent includes any one of methanol, ethanol or isopropanol, or a combination of at least two of them.

[0031] Preferably, the strong base includes any one of sodium hydroxide, lithium hydroxide or potassium hydroxide, or a combination of at least two thereof.

[0032] Preferably, the raw materials for the alcoholysis reaction include 40-60 parts of the polymer, for example, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts, 58 parts or 60 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; 180-240 parts of the alcohol solvent, for example, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts or 240 parts, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The values ​​are also applicable; 15-30 parts of strong base, for example, it can be 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but are not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; 150-300 parts of water, for example, it can be 150 parts, 160 parts, 180 parts, 200 parts, 220 parts, 240 parts, 260 parts, 280 parts or 300 parts, but are not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0033] In a second aspect, the present invention provides a method for preparing the electrode binder according to the first aspect of the present invention, the preparation method comprising the following steps:

[0034] (1) Polymerization reaction: using Class I monomer, Class II monomer and Class III monomer to carry out polymerization reaction to obtain a polymer;

[0035] (2) alcoholysis reaction: subjecting the polymer obtained in step (1) to alcoholysis reaction, and then filtering to obtain a water-soluble high molecular polymer;

[0036] (3) Dissolving: mixing the water-soluble high molecular polymer obtained in step (2) with a solvent to obtain a first solution; mixing an amino-containing polymer with a solvent to obtain a second solution;

[0037] (4) Compounding: mixing the first solution and the second solution obtained in step (3) to obtain an electrode adhesive.

[0038] The preparation method provided by the present invention is through operations such as polymerization reaction, alcoholysis reaction, dissolution, and compounding. On the one hand, the obtained water-soluble high molecular polymer has groups such as hydroxyl, carboxyl and cyano. On the other hand, the water-soluble high molecular polymer and the amino-containing polymer are compounded to form a more solid network structure. The electrode adhesive finally obtained helps to improve the flexibility and processing performance of the electrode plate.

[0039] Preferably, the preparation method specifically comprises the following steps:

[0040] (1) Polymerization reaction: water, protective gel and electrolyte are mixed to obtain a mixed solution A, an initiator and a monomer are mixed to obtain a mixed solution B, the mixed solution B is added to the mixed solution A for polymerization reaction, and then filtered to obtain a polymer;

[0041] (2) alcoholysis reaction: the polymer obtained in step (1) is mixed with an alcohol solvent to obtain a mixed solution C, a strong base is mixed with water to obtain a mixed solution D, the mixed solution D is added to the mixed solution C for alcoholysis reaction, and then filtered to obtain a water-soluble high molecular polymer;

[0042] (3) Dissolving: mixing the water-soluble high molecular polymer obtained in step (2) with a solvent to obtain a first solution; mixing an amino-containing polymer with a solvent to obtain a second solution;

[0043] (4) Compounding: mixing the first solution and the second solution obtained in step (3) to obtain an electrode adhesive.

[0044] Preferably, the polymerization reaction in step (1) comprises suspension polymerization.

[0045] Preferably, the polymerization reaction temperature is 40-70°C, for example, 40°C, 42°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the polymerization reaction time is 3-5 h, for example, 3 h, 3.2 h, 3.5 h, 3.8 h, 4 h, 4.2 h, 4.5 h, 4.8 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the temperature of the alcoholysis reaction in step (2) is 10-60°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 20-50°C.

[0048] Preferably, the alcoholysis reaction time is 1-4 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] In the present invention, by preferably controlling the temperature and time of the alcoholysis reaction within a specific range, the reaction can be effectively controlled to occur in the polymer side chain rather than the main chain. It is worth noting that when the temperature of the alcoholysis reaction is too low, the reaction occurs slowly; when the reaction temperature is too high, the main chain is easily broken to generate small molecular fragments, which lose the adhesive effect.

[0050] Preferably, an organic solvent is added before the filtration in step (2) to precipitate the water-soluble high molecular polymer.

[0051] Preferably, the organic solvent comprises ethanol.

[0052] Preferably, after filtering in step (2), drying and grinding are performed in sequence to obtain a powdered water-soluble high molecular polymer.

[0053] Preferably, the mixing temperature in the preparation of the first solution in step (3) is 50-80°C, for example, it can be 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the mixing time in the preparation of the first solution is 1-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In the present invention, by preferably controlling the dissolution temperature and time in the preparation of the first solution, the production efficiency can be effectively improved, which not only ensures sufficient dissolution, but also facilitates production operation. It is worth noting that when the dissolution temperature is too low, it is easy to cause the system viscosity to be too high, which is not conducive to production transfer.

[0056] Preferably, the solvents of the first solution and the second solution each independently comprise water.

[0057] Preferably, the mass percentage of the polymer in the first solution is 5-15%, for example, 5%, 6%, 8%, 10%, 12%, 14% or 15%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the mass percentage of the polymer in the second solution is 1-20%, for example, it can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the mixing in step (4) comprises 80-150 parts by weight of the first solution, for example, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 105 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts or 150 parts, but are not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable; and 1-10 parts of the second solution, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but are not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable.

[0060] In a third aspect, the present invention provides a use of the electrode binder according to the first aspect of the present invention, wherein the electrode binder is used for lithium-ion battery electrodes.

[0061] The electrode adhesive provided by the present invention is used for lithium ion battery electrodes, and the hydroxyl groups contained therein can form hydrogen bonds with the hydroxyl groups on the surface of the electrode negative electrode material to form a cross-linked network; and the cyano group can effectively improve the carrier migration, which is helpful to improve the battery performance; in addition, the addition of the amino polymer can provide more abundant cross-linking sites for the linear water-soluble high molecular polymer to form a more solid network structure. Therefore, the electrode adhesive provided by the present invention can effectively ensure the processing performance and use performance of the electrode and meet the requirements of lithium ion batteries.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] (1) The electrode adhesive provided by the present invention uses a homemade water-soluble high molecular polymer, which contains abundant hydroxyl and carboxyl groups on the polymer side chains, which can make it have good hydrophilicity, and the hydroxyl groups on the side chains can form hydrogen bonds with the hydroxyl groups on the surface of the electrode negative electrode material, thereby forming a cross-linked network in the electrode active material, improving its cohesion and bonding properties; the side chains of the water-soluble high molecular polymer contain cyanide groups, which can effectively improve carrier migration and help improve battery performance.

[0064] (2) The present invention provides a water-soluble high molecular polymer that has the properties of both polyvinyl alcohol and polyacrylic acid, and can further improve cohesion and flexibility.

[0065] (3) The electrode adhesive provided by the present invention adopts a compound of a water-soluble high molecular polymer and an amino-containing polymer. The addition of the amino polymer can provide more abundant cross-linking sites for the linear water-soluble high molecular polymer, form a more solid network structure, and effectively disperse the internal stress of the polymer itself, thereby further improving the flexibility and processing performance of the electrode plate.

[0066] (4) Specifically, under optimal conditions, the adhesive provided by the present invention can achieve a bonding strength of 9.5 N / m or more after rolling, a swelling rate of 17% or less, and a flexibility of 3 mm or less. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] In the following examples and comparative examples, polyvinyl alcohol is selected from Sichuan Wei Chemical Industry with a brand name of 1788; polyethyleneimine is selected from BASF's Lupasol series Lupasol P; and polymelamine resin is selected from allnex CYMEL series CYMEL350.

[0069] Example 1

[0070] The present embodiment provides an electrode adhesive, which includes a water-soluble high molecular polymer and an amino-containing polymer. The amino-containing polymer is polyethyleneimine, which is obtained by sequentially performing polymerization reaction and alcoholysis reaction on monomers. The monomers include Class I monomers, Class II monomers and Class III monomers. Class I monomers are vinyl acetate, Class II monomers are methyl acrylate, and Class III monomers are acrylonitrile. The mass ratio of Class I monomers, Class II monomers and Class III monomers is 50:15:5.

[0071] This embodiment also provides a method for preparing the electrode binder, the method comprising the following steps:

[0072] (1) Polymerization reaction: water, protective gel and electrolyte are mixed in a reactor, stirred to dissolve, and a mixed solution A is obtained; an initiator and a monomer are mixed, stirred to dissolve the initiator, and a mixed solution B is obtained; the mixed solution B is added dropwise to the mixed solution A through a peristaltic pump for 3 hours; the polymerization reaction is carried out at 50° C. for 4 hours, and then the material is cooled, discharged, and filtered to obtain a polymer;

[0073] (2) alcoholysis reaction: the polymer obtained in step (1) and an alcohol solvent are mixed and stirred to dissolve to obtain a mixed solution C, a strong base and water are mixed to obtain a mixed solution D, the mixed solution D is added dropwise to the mixed solution C using a peristaltic pump and an alcoholysis reaction is carried out at 50° C. for 3 h, then the temperature is lowered, 400 parts of ethanol is added to precipitate a water-soluble high molecular polymer, and then filtered, dried, and ground to obtain a powdered water-soluble high molecular polymer;

[0074] (3) Dissolving: mixing the water-soluble polymer obtained in step (2) with water at 70° C. for 4 hours to obtain a first solution; mixing an amino-containing polymer with water to obtain a second solution;

[0075] (4) Compounding: Mix the first solution and the second solution obtained in step (3), and continue stirring for 1 hour to obtain an electrode adhesive.

[0076] In this embodiment, the components and amounts used in the preparation method are shown in Table 1.

[0077] Example 2

[0078] The present embodiment provides an electrode adhesive, which includes a water-soluble high molecular polymer and an amino-containing polymer. The amino-containing polymer is polyethyleneimine, which is obtained by sequentially performing polymerization reaction and alcoholysis reaction on monomers. The monomers include Class I monomers, Class II monomers and Class III monomers. Class I monomer is vinyl propionate, Class II monomer is butyl acrylate, and Class III monomer is acrylonitrile.

[0079] This embodiment also provides a method for preparing the electrode binder, the method comprising the following steps:

[0080] (1) Polymerization reaction: water, protective gel and electrolyte are mixed in a reactor, stirred to dissolve, and a mixed solution A is obtained; an initiator and a monomer are mixed, stirred to dissolve the initiator, and a mixed solution B is obtained; the mixed solution B is added dropwise to the mixed solution A through a peristaltic pump and a polymerization reaction is carried out at 40° C. for 5 h, and then the material is cooled, discharged, and filtered to obtain a polymer;

[0081] (2) alcoholysis reaction: the polymer obtained in step (1) and an alcohol solvent are mixed and stirred to dissolve to obtain a mixed solution C, a strong base and water are mixed to obtain a mixed solution D, the mixed solution D is added dropwise to the mixed solution C using a peristaltic pump and the mixed solution is subjected to alcoholysis reaction at 45° C. for 4 h, then the temperature is lowered, 400 parts of ethanol is added to precipitate a water-soluble high molecular polymer, and then filtered, dried, and ground to obtain a powdered water-soluble high molecular polymer;

[0082] (3) Dissolving: mixing the water-soluble polymer obtained in step (2) with water at 80° C. for 3 hours to obtain a first solution; mixing an amino-containing polymer with water to obtain a second solution;

[0083] (4) Compounding: Mix the first solution and the second solution obtained in step (3), and continue stirring for 1 hour to obtain an electrode adhesive.

[0084] In this embodiment, the components and amounts used in the preparation method are shown in Table 1.

[0085] Example 3

[0086] The present embodiment provides an electrode adhesive, which includes a water-soluble high molecular polymer and an amino-containing polymer. The amino-containing polymer is polyethyleneimine, which is obtained by sequentially performing polymerization reaction and alcoholysis reaction on monomers. The monomers include Class I monomers, Class II monomers and Class III monomers. Class I monomers are vinyl acetate, Class II monomers are methyl acrylate, and Class III monomers are acrylonitrile.

[0087] This embodiment also provides a method for preparing the electrode binder, the method comprising the following steps:

[0088] (1) Polymerization reaction: water, protective gel and electrolyte are mixed in a reactor, stirred to dissolve, and a mixed solution A is obtained; an initiator and a monomer are mixed, stirred to dissolve the initiator, and a mixed solution B is obtained; the mixed solution B is added dropwise to the mixed solution A through a peristaltic pump and a polymerization reaction is carried out at 70° C. for 3 h, and then the material is cooled, discharged, and filtered to obtain a polymer;

[0089] (2) alcoholysis reaction: the polymer obtained in step (1) and an alcohol solvent are mixed and stirred to dissolve to obtain a mixed solution C, a strong base and water are mixed to obtain a mixed solution D, the mixed solution D is added dropwise to the mixed solution C using a peristaltic pump and the mixed solution is subjected to alcoholysis reaction at 35° C. for 2 h, then the temperature is lowered, 400 parts of ethanol is added to precipitate a water-soluble high molecular polymer, and then filtered, dried, and ground to obtain a powdered water-soluble high molecular polymer;

[0090] (3) Dissolving: mixing the water-soluble high molecular polymer obtained in step (2) with water at 60° C. for 2 hours to obtain a first solution; mixing an amino-containing polymer with water to obtain a second solution;

[0091] (4) Compounding: Mix the first solution and the second solution obtained in step (3), and continue stirring for 1 hour to obtain an electrode adhesive.

[0092] In this embodiment, the components and amounts used in the preparation method are shown in Table 1.

[0093] Example 4

[0094] This embodiment provides an electrode adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the alcohol solvent is replaced by methanol.

[0095] Example 5

[0096] This embodiment provides an electrode adhesive and a preparation method thereof. The only difference compared with Embodiment 1 is that the pH of the alcoholysis reaction is kept constant and 20 parts of sodium hydroxide are replaced by 25 parts of lithium hydroxide.

[0097] Example 6

[0098] This embodiment provides an electrode binder and a preparation method thereof, which is different from Embodiment 1 only in that the amino-containing polymer is replaced by polymelamine.

[0099] Example 7

[0100] This embodiment provides an electrode adhesive and a preparation method thereof. The only difference compared with Example 1 is that the total number of monomers is kept unchanged, and the number of Class I monomer vinyl acetate is adjusted to 28 parts, the number of Class II monomer methyl acrylate is adjusted to 28 parts, and the number of Class III monomer acrylonitrile is adjusted to 14 parts.

[0101] Example 8

[0102] This embodiment provides an electrode adhesive and a preparation method thereof. The only difference compared with Example 1 is that the total number of monomers is kept unchanged, and the number of Class I monomer vinyl acetate is adjusted to 62 parts, the number of Class II monomer methyl acrylate is adjusted to 3 parts, and the number of Class III monomer acrylonitrile is adjusted to 5 parts.

[0103] The components and amounts used in the preparation methods described in Examples 4-8 are shown in Table 1. The data in Table 1 represent parts by weight.

[0104] Table 1

[0105]

[0106]

[0107] Example 9

[0108] This embodiment provides a method for preparing an electrode binder, which is different from Embodiment 1 only in that the temperature of the alcoholysis reaction is 10°C.

[0109] Example 10

[0110] This embodiment provides a method for preparing an electrode binder, which is different from Embodiment 1 only in that the temperature of the alcoholysis reaction is 60°C.

[0111] Embodiment 11

[0112] This embodiment provides a method for preparing an electrode binder, which is different from Embodiment 1 only in that the mixing time in the preparation of the first solution is 6 hours.

[0113] Comparative Example 1

[0114] This comparative example provides an electrode adhesive and a preparation method thereof. The only difference compared with Example 1 is that the electrode adhesive is only a first solution and is not compounded with a second solution.

[0115] Comparative Example 2

[0116] This comparative example provides an electrode adhesive and a preparation method thereof. The only difference compared with Example 1 is that the electrode adhesive is only the second solution and is not compounded with the first solution.

[0117] Performance Testing:

[0118] (1) Physical property test:

[0119] After the adhesive samples prepared in the embodiments and comparative examples are cooled to 25°C, their pH value is tested with a pH meter; their viscosity is tested with a viscometer; 2-3 g of the adhesive is taken, weighed (recorded as M1), and then placed in an oven at 150°C for 30 min, weighed (recorded as M2), and the solid content is calculated: solid content = M2 / M1×100%.

[0120] (2) Bond strength:

[0121] The electrode active material artificial graphite, conductive carbon black (SP), binder and water were dispersed at high speed for 1 hour to prepare a viscous slurry (solid content of 52wt%). After standing for 1 hour, the slurry was coated on a copper foil by an automatic coating machine and dried at 105°C for 5 minutes to obtain an electrode sheet; the mass ratio of the electrode active material, SP and binder was 97:1:2, and the surface density of the coated electrode was 8g / cm 2 .

[0122] The electrode sheet was rolled through a roller press with a pressure of 8MPa, and the peeling bond strength before and after rolling was tested. The specific method is: the electrode sheet copper foil was cut into 5cm×10cm, and the side coated with slurry was pasted on the 3M tape, and the 3M tape was pasted on the stainless steel plate. After the sample was prepared, the stainless steel plate was fixed with a universal tensile machine, and the electrode sheet copper foil was peeled off 180° from the stainless steel plate. To ensure the accuracy of the results, each sample was tested five times, and the highest and lowest values ​​were removed. The remaining values ​​were averaged, which was the bonding strength data.

[0123] (3) Electrolyte swelling resistance:

[0124] 15g of adhesive sample was placed in a mold and dried at 65℃ for 72h. Then the middle part was selected to cut a 1.5×1.5cm 2 For a sample of about 3 mm in size and thickness, accurately weigh the sample mass, recorded as m1. Soak the sample in the electrolyte, place it at 65°C for 72 hours, then take it out and use dust-free paper to absorb the residual liquid on the surface. Weigh the sample mass again, recorded as m2. The swelling rate data is calculated using the following formula: swelling rate = (m2-m1) / m1×100%.

[0125] (4) Flexibility test:

[0126] The prepared electrode sheet is put through the cylinder test. The test method is: fix the cylinder on the base, pass the electrode sheet through the cylinder, bend it 180°, remove the electrode sheet, and observe the crease at the bend. If there is no obvious mark, it means it has passed. Select a cylinder with a smaller diameter to repeat the test until a crease appears. Record the minimum cylinder diameter that passes the test. The smaller the value, the higher the flexibility.

[0127] The data of the above Examples 1-11 and Comparative Examples 1-2 are shown in Table 2.

[0128] Table 2

[0129]

[0130]

[0131] From the data in Table 2, we can see the following points:

[0132] (1) From the data of Examples 1-6, it can be seen that under optimal conditions, the adhesive provided by the present invention can achieve a bonding strength of 9.5 N / m or more after rolling, a swelling rate of 17% or less, and a flexibility of 3 mm or less.

[0133] (2) Comprehensive comparison of the data of Example 1 and Examples 7-8 shows that the only difference between Example 7-8 and Example 1 is that the mass ratio of Class I monomers, Class II monomers and Class III monomers is not within the preferred range of the present invention. The bonding strength after rolling in Example 1 is significantly higher than that in Examples 7-8, the swelling resistance is significantly better than that in Example 8, and the flexibility is significantly better than that in Example 7. It can be seen that the present invention can further improve the comprehensive performance of the adhesive by preferentially controlling the mass ratio of Class I monomers, Class II monomers and Class III monomers.

[0134] (3) Comprehensive comparison of the data of Example 1 and Examples 9-11 shows that the present invention can further ensure adhesion, swelling resistance and flexibility by preferably controlling the temperature of the alcoholysis reaction. The present invention can further ensure that the polymer is fully dissolved by preferably controlling the mixing time in the preparation of the first solution, thereby further improving adhesion.

[0135] (4) A comprehensive comparison of the data of Example 1 and Comparative Examples 1-2 shows that the adhesive provided by the present invention can improve the bonding strength and flexibility after rolling by compounding a water-soluble high molecular polymer and an amino-containing polymer, compared with using only one polymer.

[0136] In summary, the electrode adhesive provided by the present invention has good bonding performance and flexibility, and is resistant to electrolyte swelling, and is suitable for electrode materials of lithium ion batteries.

[0137] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An electrode adhesive, characterized in that: The electrode binder comprises a water-soluble high molecular polymer and an amino-containing polymer; The water-soluble high molecular polymer is obtained by sequentially performing polymerization reaction and alcoholysis reaction on monomers; The monomers include class I monomers, class II monomers and class III monomers; The Class I monomers include vinyl acetate and / or vinyl propionate; The type II monomers include methacrylates containing short-chain alkanes and / or acrylates containing short-chain alkanes; The class III monomers contain a cyano group.

2. The electrode binder according to claim 1, characterized in that The amino-containing polymer includes any one of polyethyleneimine, polymelamine or polymelamine formal, or a combination of at least two of them.

3. The electrode binder according to claim 1 or 2, characterized in that: The short-chain alkanes in the class II monomers include alkanes with carbon atoms ≤ 4; Preferably, the type II monomer includes any one or a combination of at least two of methyl acrylate, methyl methacrylate, butyl acrylate or ethyl acrylate; Preferably, the Class III monomers include acrylonitrile and / or methacrylonitrile; Preferably, the raw materials for the polymerization reaction also include water, protective colloid, electrolyte and initiator; Preferably, the protective colloid comprises polyvinyl alcohol and / or polyvinyl pyrrolidone; Preferably, the electrolyte comprises sodium bicarbonate and / or sodium sulfate; Preferably, the initiator comprises an azo compound and / or a peroxide; Preferably, the azo compound includes azobisisoheptanitrile and / or azobisisobutyronitrile; Preferably, the peroxide comprises diisopropyl peroxydicarbonate and / or lauroyl peroxide; Preferably, the raw materials for the polymerization reaction include, by weight, 20-70 parts of Class I monomers, 10-40 parts of Class II monomers, 1-20 parts of Class III monomers, 0.1-0.5 parts of initiators, 1-5 parts of protective colloids, 0.1-0.5 parts of electrolytes, and 150-300 parts of water; Preferably, the mass ratio of the class I monomer, the class II monomer and the class III monomer is (40-60):(15-25):(5-15); Preferably, the weight average molecular weight of the water-soluble high molecular polymer is 500-1000 kDa.

4. The electrode binder according to any one of claims 1 to 3, characterized in that: The raw materials of the alcoholysis reaction include polymer, alcohol solvent, strong base and water; Preferably, the alcohol solvent includes any one of methanol, ethanol or isopropanol or a combination of at least two thereof; Preferably, the strong base includes any one of sodium hydroxide, lithium hydroxide or potassium hydroxide, or a combination of at least two thereof; Preferably, the raw materials for the alcoholysis reaction include, by weight, 40-60 parts of polymer, 180-240 parts of alcohol solvent, 15-30 parts of strong base, and 150-300 parts of water.

5. A method for preparing an electrode binder according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Polymerization reaction: using Class I monomer, Class II monomer and Class III monomer to carry out polymerization reaction to obtain a polymer; (2) alcoholysis reaction: subjecting the polymer obtained in step (1) to alcoholysis reaction, and then filtering to obtain a water-soluble high molecular polymer; (3) Dissolving: mixing the water-soluble high molecular polymer obtained in step (2) with a solvent to obtain a first solution; mixing an amino-containing polymer with a solvent to obtain a second solution; (4) Compounding: mixing the first solution and the second solution obtained in step (3) to obtain an electrode adhesive.

6. The preparation method according to claim 5, characterized in that: The preparation method specifically comprises the following steps: (1) Polymerization reaction: water, protective gel and electrolyte are mixed to obtain a mixed solution A, an initiator and a monomer are mixed to obtain a mixed solution B, the mixed solution B is added to the mixed solution A for polymerization reaction, and then filtered to obtain a polymer; (2) alcoholysis reaction: the polymer obtained in step (1) is mixed with an alcohol solvent to obtain a mixed solution C, a strong base is mixed with water to obtain a mixed solution D, the mixed solution D is added to the mixed solution C for alcoholysis reaction, and then filtered to obtain a water-soluble high molecular polymer; (3) Dissolving: mixing the water-soluble high molecular polymer obtained in step (2) with a solvent to obtain a first solution; mixing an amino-containing polymer with a solvent to obtain a second solution; (4) Compounding: mixing the first solution and the second solution obtained in step (3) to obtain an electrode adhesive.

7. The preparation method according to claim 6, characterized in that: The polymerization reaction in step (1) comprises suspension polymerization; Preferably, the polymerization reaction temperature is 40-70°C; Preferably, the polymerization reaction time is 3-5h.

8. The preparation method according to claim 6 or 7, characterized in that: The temperature of the alcoholysis reaction in step (2) is 10-60°C, preferably 20-50°C; Preferably, the alcoholysis reaction time is 1-4h; Preferably, an organic solvent is added before filtering in step (2) to precipitate the water-soluble high molecular polymer; Preferably, the organic solvent comprises ethanol; Preferably, after filtering in step (2), drying and grinding are performed in sequence to obtain a powdered water-soluble high molecular polymer.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The mixing temperature in the preparation of the first solution in step (3) is 50-80° C.; Preferably, the mixing time in the preparation of the first solution is 1-5h; Preferably, the solvents of the first solution and the second solution each independently comprise water; Preferably, the mass percentage of the polymer in the first solution is 5-15%; Preferably, the mass percentage of the polymer in the second solution is 1-20%; Preferably, the mixing in step (4) comprises 80-150 parts of the first solution and 1-10 parts of the second solution in parts by weight.

10. A use of the electrode binder according to any one of claims 1 to 4, characterized in that: The electrode binder is used for lithium ion battery electrodes.

Citation Information

Patent Citations

  • Curable composition, bonding method and bonded body

    CN101622287A

  • Water-soluble electrode binder, electrode plate and preparation method thereof, and electrochemical energy storage device

    CN108933260A

  • Multipurpose double-component composite adhesive with high solid content and preparation method and application thereof

    CN110105902A

  • Aqueous polymer for adhesive and preparation method, aqueous adhesive and silicon cathode lithium ion battery

    CN110423301A

  • Water-based adhesive as well as preparation method and application thereof

    CN110616055A

Cited By

  • Silicon negative electrode material adhesive as well as preparation method and application thereof

    CN120025766A

  • A silicon anode material binder, its preparation method and application

    CN120025766B